The potential of sodium-glucose cotransporter 2 inhibitors for the treatment of systemic right ventricular failure in adults with congenital heart disease - Neijenhuis, Ralph M. L.; Nederend, Marieke; Jongbloed, Monique R. M.; Kiès, Philippine; Rotmans, Joris I.; Vliegen, Hubert W.; Jukema, J. Wouter; Egorova, Anastasia D. (Frontiers in Cardiovascular Medicine, 2023)
Aims Given the compelling evidence on the effectiveness of sodium-glucose cotransporter 2 inhibitors (SGLT2i) in the conventional heart failure population, SGLT2i deserve exploration in systemic right ventricular (sRV) failure. The initial experience with dapagliflozin in sRV failure patients is described, with a focus on tolerability and short-term effects on clinical outcomes. Methods and results Ten patients (70% female, median age 50 years [46.5–52]) with symptomatic sRV failure who received dapagliflozin 10 mg per day on top of optimal medical therapy between 04–2021 and 01–2023 were included. Within 4 weeks, no significant changes in blood pressure, electrolytes, or serum glucose occurred. Creatinine and estimated glomerular filtration rate (eGFR) showed a slight decline (88 ± 17 to 97 ± 23 µmol/L, p = 0.036, and 72 ± 14 vs. 66 ± 16 ml/min/1.73m2, p = 0.020, respectively). At 6 months follow-up (n = 8), median NT-proBNP decreased significantly from 736.6 [589.3–1193.3] to 531.6 [400.8–1018] ng/L (p = 0.012). Creatinine and eGFR recovered to baseline levels. There were no significant changes in echocardiographic systolic sRV or left ventricular function. New York Heart Association class improved significantly in 4 out of 8 patients (p = 0.046), who also showed an improvement in the 6-minute walk test or bicycle exercise test performance. One female patient developed an uncomplicated urinary tract infection. No patients discontinued treatment. Conclusion Dapagliflozin was well-tolerated in this small cohort of sRV failure patients. While the early results on the reduction of NT-proBNP and clinical outcome parameters are encouraging, large-scale prospective studies are warranted to thoroughly evaluate the effects of SGLT2i in the growing sRV failure population.